2022
DOI: 10.1039/d2gc02927h
|View full text |Cite
|
Sign up to set email alerts
|

An air chargeable hydrogen battery by reversible electrochemical trapping of the protons

Abstract: An air chargeable hydrogen battery is demonstrated by reversible trapping of the protons, in a hydrogen carrying quinone moiety. Charging the battery with ambient air without any electrical supply, adds an extra handle to battery functionality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Recently, it is also found materials of high capacities comparable with battery electrodes like Pyrene‐4,5,9,10‐tetraone (PTO, up to 400 mAh g −1 accompanied with representative plateaus, see Figure 7c), [ 51 ] which stimulates the development of proton batteries with fast rate‐capabilities. [ 57 ] There are other reports of quinone‐based proton electrodes, such as anthraquinone (AQ), [ 58 ] benzoquinone (BQ), [ 59,60 ] 3,4,9,10‐perylenetetracarboxylic dianhydride (PTCDA), [ 22 ] p‐chloranil, [ 33 ] tetramethylquinone (TMBQ), [ 61 ] etc.…”
Section: Faradaic Electrodes For Proton Storagementioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it is also found materials of high capacities comparable with battery electrodes like Pyrene‐4,5,9,10‐tetraone (PTO, up to 400 mAh g −1 accompanied with representative plateaus, see Figure 7c), [ 51 ] which stimulates the development of proton batteries with fast rate‐capabilities. [ 57 ] There are other reports of quinone‐based proton electrodes, such as anthraquinone (AQ), [ 58 ] benzoquinone (BQ), [ 59,60 ] 3,4,9,10‐perylenetetracarboxylic dianhydride (PTCDA), [ 22 ] p‐chloranil, [ 33 ] tetramethylquinone (TMBQ), [ 61 ] etc.…”
Section: Faradaic Electrodes For Proton Storagementioning
confidence: 99%
“…In 2022, the same group reported updates with an air‐chargeable hydrogen battery chemistry by introducing an additional air cathode as shown in Figure 15c. [ 59 ] During discharge, the battery consumes hydrogen and stores proton in quinone moiety while delivering electric power (H 2 ‐BQ discharge), and the redox energy positioning of molecule oxygen above that of hydroquinone allows the battery charging with ambient air during concomitant electric power production. Also, Cui and co‐workers [ 32 ] proposed another concept of a manganese‐hydrogen battery in 2018 that compensates for the charge of catalytic HER/HOR by the electrolysis of MnO 2 /Mn 2+ in a singular acidic electrolyte of MnSO 4 and H 2 SO 4 , as shown in Figure 15d.…”
Section: Faradaic Electrodes For Proton Storagementioning
confidence: 99%
See 1 more Smart Citation
“…12,37 We therefore hypothesize that the performance of organic proton batteries can be enhanced using a catalytic hydrogen anode. Although a benzoquinone (BQ)-H 2 battery has been proposed previously, 42,43 it was implemented in a membrane electrode assembly that requires the use of expensive Nafion membranes, which sacrificed the low-cost advantage of organic electrodes. In addition, the limited solubility of BQ molecules in aqueous solutions leads to a low energy density for the BQ-H 2 battery.…”
mentioning
confidence: 99%
“…Hydrogen, as a green fuel, has made remarkable progress in the field of rechargeable hydrogen gas batteries based on the anode hydrogen evolution and oxidation reaction (HER/ HOR) redox couple. , As an emerging anode, the HER/HOR reaction has the advantages of low overpotential, fast reaction kinetics, and superb stability. , Chen’s group has demonstrated that the hydrogen electrode can achieve fast kinetics and long cycle life in aqueous batteries. ,,, For example, excellent rate performance of 100 C and long-term cycle life of over 50000 cycles have been achieved in Prussian blue analogue-H 2 APBs. , We therefore hypothesize that the performance of organic proton batteries can be enhanced using a catalytic hydrogen anode. Although a benzoquinone (BQ)-H 2 battery has been proposed previously, , it was implemented in a membrane electrode assembly that requires the use of expensive Nafion membranes, which sacrificed the low-cost advantage of organic electrodes. In addition, the limited solubility of BQ molecules in aqueous solutions leads to a low energy density for the BQ-H 2 battery.…”
mentioning
confidence: 99%